Cross-cultural validation of the Fukushima lumbar spinal stenosis scale in Korean patients with degenerative lumbar spinal stenosis - Il-Soo Eun; Hak Sang Kim; Yoon Jae Cho; Tae Sik Goh; Jung Sub Lee (Journal of Orthopaedic Surgery and Research)
Abstract Background The Fukushima Lumbar Spinal Stenosis Scale (FLS-25) is a disease-specific patient-reported outcome measure developed to assess the symptoms and functional impact of lumbar spinal stenosis (LSS). However, no Korean version of the FLS-25 has been validated to date. This study aimed to assess the reliability, validity, and responsiveness of a Korean adaptation of the FLS-25 (K-FLS-25) using a structured cross-cultural adaptation process. Methods The original FLS-25 questionnaire was translated into Korean following established guidelines for cross-cultural adaptation, including forward translation, synthesis, back-translation, expert committee review, and pretesting. The finalized Korean version (K-FLS-25) was initially administered to 140 consecutive patients diagnosed with LSS. Of these, 123 patients completed both the baseline and follow-up assessments and were included in the final analysis. To evaluate construct validity, participants also completed the validated Korean version of the Oswestry Disability Index (ODI) and a Visual Analog Scale (VAS) for back and leg pain. Reliability was assessed through item-wise agreement using kappa statistics, test-retest reliability via the intraclass correlation coefficient (ICC [2,1]), and internal consistency using Cronbach’s α. Construct validity was evaluated by calculating Pearson’s correlation coefficients between K-FLS-25, ODI, and VAS scores. Results All items of the K-FLS-25 demonstrated substantial agreement, with kappa values exceeding 0.6. The test-retest reliability was excellent (ICC [2,1] = 0.93), and internal consistency was high (Cronbach’s α = 0.901). Construct validity was supported by significant Pearson’s correlation coefficients between the total and domain scores of K-FLS-25 and the scores of the ODI and VAS for both back and leg pain. As part of cultural adaptation, a prefinal version was tested in 30 Korean-speaking LSS patients, who reported good comprehension without major issues. The final version was confirmed by expert consensus. Conclusions The K-FLS-25 was successfully translated and culturally adapted for Korean-speaking patients. It demonstrated excellent reliability, validity, and responsiveness, supporting its suitability as a disease-specific instrument for evaluating symptoms, functional disability, and treatment-related changes in patients with lumbar spinal stenosis in Korea.